The Influence Of Students’ Self-Efficacy And Teacher Competence On Academic Achievement Through Learning Motivation - Novie Bataini Syamsurijal Safitri; Kadeni Kadeni; M. Abdul Roziq Asrori (PT. Anagata Sembagi Education, 2025)
This study aims to analyse the influence of self-efficacy and teacher competence on students’ academic achievement, with learning motivation as a mediating variable. Self-efficacy is defined as students’ belief in their ability to accomplish academic tasks, while teacher competence encompasses pedagogical, professional, social, and personal dimensions that affect instructional quality. The research employed a quantitative associative approach using a descriptive-correlational non-experimental design. The sample consisted of 217 students selected through proportional random sampling. Data were collected using a structured and validated questionnaire tested for reliability. Data analysis was performed using Structural Equation Modeling (SEM) with the SmartPLS application. The results indicate that both self-efficacy and teacher competence have a positive and significant influence on learning motivation, and that learning motivation mediates the relationship between these variables and academic achievement. Furthermore, self-efficacy and teacher competence also exert a direct effect on academic achievement. These findings highlight the importance of enhancing students’ self-efficacy and improving teacher competence in order to foster academic success through students’ intrinsic motivation.